Orthogonal Full-Field Optical Sampling - Janosch Meier; Arijit Misra; Stefan Preusler; Thomas Schneider (IEEE Photonics Journal, 2019)
Sampling is the first step to convert analogue into digital signals and one of the basic concepts for information handling. All practical sampling systems, however, are accompanied with errors. Bandwidth-limited signals can be seen as a superposition of time-shifted sinc pulses, weighted with the sampling values. Thus, due to orthogonality, bandlimited signals can be perfectly sampled by a corresponding sinc pulse with the correct time shift. But, sinc pulses are just a mathematical construct. Sinc pulse sequences, instead, can simply be generated by a rectangular, phase-locked frequency comb. For a high repetition-time to pulsewidth ratio, or a low duty cycle, the pulses of such a sequence come close to single sinc pulses, and thus, the sampling with them might lead to an almost ideal sampling. Here, we present the full-field optical sampling with a repetition-time to pulsewidth ratio of up to 153, or a duty cycle of around 0.65%. Since it enables amplitude and phase sampling, ultrahigh sampling rates should be possible.